Organizational wrongdoing as the "foundational" grand challenge : consequences and impact - Gabbioneta, Claudia; Clemente, Marco; Greenwood, Royston (Research in the sociology of organizations ;, 2023)
Media coverage consistently features examples of organizations engaging in unethical or illegal behavior. Given its potential to impact and even damage established institutions, organizational wrongdoing deserves to be closely monitored and more carefully examined. Drawing attention to the theoretical and empirical relevance of this topic, this second instalment in a double volume of Research in the Sociology of Organizations focuses on the consequences of organizational wrongdoing, the role of whistleblowing, and methodological issues. Detailing the ramifications of organizational wrongdoing, chapters in this second volume examine the remedial actions that firms can take to recover from wrongdoing, the so-called spill over effects of organizational wrongdoing whereby 'innocent' firms are affected by the misdeeds committed by others, as well as the valuable insights that historical approaches can provide in studying organizational wrongdoing. Taken individually as well as together, the two volumes that comprise Organizational Wrongdoing as the "Foundational" Grand Challenge provide a major touchstone for scholars interested in understanding recent developments and exciting new directions in the study of organizational wrongdoing.